[Wanted Site for trash ; Logging in Laguna ; Color my world [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
Discusses the residents complaint on the location of dumpsites by the government in Camarin, Caloocan City; illegal logging in Majayjay, Laguna; and the color fashion tip.
Wanted: Site for trash (12 min.) -- Logging Laguna (10 min.) -- Color my world (11 min.)
VHS.
Keywords: Waste disposal sites -- Philippines -- Camarin (Caloocan City).; Logging -- Philippines -- Majayjay (Laguna).; Fashion -- Philippines